2022
DOI: 10.3390/agriculture12060868
|View full text |Cite
|
Sign up to set email alerts
|

Farrowing Pens for Individually Loose-Housed Sows: Results on the Development of the SowComfort Farrowing Pen

Abstract: The objective of the present paper was to discuss the design of farrowing pens and present the first production results of the “SowComfort farrowing pen” (SOWCOMF). The biggest difference between this pen and the traditional pen (TRAD) presented in the study, is that SOWCOMF contains a nest area equipped with a rubber mattress, floor heating, a rack for straw and no separate creep area. It was predicted that SOWCOMF would result in lower piglet mortality compared to TRAD due to a more stimulating and comfortab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
10
1
Order By: Relevance
“…In the present dissertation, two alternative farrowing environments, namely the free-farrowing pen and group housing of lactating sows and litters, were compared with farrowing crates. While other studies reported benefits for the piglets from loose-housed sows in terms of the experience of maternal behaviour and a better coping strategy towards weaning stress Oostindjer et al, 2011;Andersen and Ocepek, 2022), the results of the present dissertation could only detect minor significant and numerical improvements for post-weaning stress or any positive long-term effects for piglets from freefarrowing pens compared to piglets from confined sows. In contrast, piglets from group housing showed less skin lesions after regrouping events, a smaller difference in pre-to post-weaning serum cortisol and less fighting behaviour, but tails of group housing pigs were scored slightly more often with severe and very severe tail lesions than tails of free-farrowing and farrowing crate pigs.…”
Section: Housing During Suckling Periodcontrasting
confidence: 83%
See 1 more Smart Citation
“…In the present dissertation, two alternative farrowing environments, namely the free-farrowing pen and group housing of lactating sows and litters, were compared with farrowing crates. While other studies reported benefits for the piglets from loose-housed sows in terms of the experience of maternal behaviour and a better coping strategy towards weaning stress Oostindjer et al, 2011;Andersen and Ocepek, 2022), the results of the present dissertation could only detect minor significant and numerical improvements for post-weaning stress or any positive long-term effects for piglets from freefarrowing pens compared to piglets from confined sows. In contrast, piglets from group housing showed less skin lesions after regrouping events, a smaller difference in pre-to post-weaning serum cortisol and less fighting behaviour, but tails of group housing pigs were scored slightly more often with severe and very severe tail lesions than tails of free-farrowing and farrowing crate pigs.…”
Section: Housing During Suckling Periodcontrasting
confidence: 83%
“…Besides group structure, there is also a need of improvement concerning the number of piglet losses due to crushing, as it was inexcusably high but could at least be lowered by temporary confinement of the sows that sows in the bigger pens crushed significantly less piglets than in the smaller pens (7.1 m² vs. 8.3 m²). Andersen and Ocepek (2022) who studied two types of free-farrowing pens, also found more crushed ("overlain") piglets in the smaller pens (7.7 m² vs. 8.3 m²). These findings do somehow conflict the demands of the TierSchNutztV which require even smaller farrowing pens of only 6.5 m².…”
Section: Housing During Suckling Periodmentioning
confidence: 92%
“…A well-designed and managed system without permanent crating can achieve the same performance as conventional farrowing crates. This has been demonstrated in research [e.g., (8) for review] and, perhaps more importantly, under commercial conditions [e.g., (14,38,40,115)]. Review articles attempting to summarize performance information of alternative farrowing systems have cited a number of important caveats (3,(5)(6)(7)(8); specifically that summarizing can result in loss of details of particular studies that might contribute to explaining performance outcomes.…”
Section: Performancementioning
confidence: 99%
“…This is to achieve the same piglet mortality in a FF system as a permanent crate system, but they also state a 90% certainty range from 5.7 to 11.0 m 2 because of the important interacting effects of design detail and quality of management. When interviewing/surveying farmers from countries with FF as standard, they regularly say that their minimum space regulations are not enough and typical pen sizes in operation are larger [e.g., 7.0 to 8.3 m 2 in Switzerland and Norway ( 39 , 40 ). Andersen and Ocepek ( 40 ) comment that the larger pen space in Norway is, in part, due to the future trend of building “from-farrowing-to 30 kg pens” where the piglets can remain and stay with their litter mates after weaning and the sow is moved.…”
Section: What Are the Key Decisions When Designing A New Indoor Farro...mentioning
confidence: 99%
“…Although considerable research is on-going on free farrowing systems (Google scholar search identified 4490 papers published since 2018), the UK Farm Animal Welfare Council [ 26 ] concluded that satisfactory results are not yet available, and commercial developments are not yet sufficiently advanced to allow recommendation of compulsory replacement of farrowing crates. Hansen [ 27 ] tested ten different designs of farrowing pens for loose-housed sows and recommended there are still challenges to be resolved before implementing this type of management system on a broad scale.…”
Section: Introductionmentioning
confidence: 99%